Do opponents' experience matter? Experimental evidence from a quantity precommitment game - Chloé LeCoq; Jesper Roine (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
This paper investigates why subjects in laboratory experiments on quantity precommitment games consistently choose capacities above the Cournot level - the subgame-perfect equilibrium. We argue that this puzzling regularity may be attributed to players' perceptions of their opponents' skill or level of rationality. In our experimental design, we use the level of experience (the number of periods played) as a proxy for the level of rationality and match subjects with different levels of experience. We first find evidence of capacity choices decreasing, and prices increasing, with the opponent's experience. Futhermore, we investigate the observed behavioural patterns by using the agent-form quantal response equilibrium model by McKelvey and Palfrey (1998). In particular, this framework takes into account any interaction between a player's own experience and that of his opponent. We show how the predictions of this theoretical framework fit well with the experimental data.
Keywords: C92; L13; 330; Oligopoly; Quantity precommitment; Experience; Rationality; Spieltheorie; Lernprozess; Test